Size‐Selective Feeding in Captive and Free‐Ranging Atlantic Bluefin Tuna. Issue 1 (15th April 2014) - Butler, Christopher M.; Hanrahan, Brian; Buckel, Jeffrey A.; Rudershausen, Paul J.; Juanes, Francis; Smith, Joseph W.
Abstract: We examined size‐selective feeding in captive and free‐ranging Atlantic Bluefin Tuna Thunnus thynnus . For the captive study, Bluefin Tuna were maintained in a cylindrical net‐pen enclosure (30.5 m in diameter; 15.2 m deep) located 32.2 km offshore of Virginia. Tests of prey size selectivity by captive Bluefin Tuna were observed using underwater video. In free‐ranging Bluefin Tuna, size selection was examined by comparing the sizes of Atlantic Menhaden Brevoortia tyrannus found in stomach contents with the sizes of those collected during the fall purse‐seine fishery for Atlantic Menhaden off the North Carolina coast. Captive Bluefin Tuna selected larger prey when prey length : predator length ratios (PPRs) were less than 10%; however, size selectivity was not observed when the PPRs exceeded 10%. For free‐ranging Bluefin Tuna, PPRs were mostly greater than 10% (12.98 ± 0.06% [mean ± SE]), and there were no significant differences in length between Atlantic Menhaden from stomach contents and those from purse‐seine collections. The minimum and median sizes of Atlantic Menhaden prey increased with increasing predator size; however, the maximum size of Atlantic Menhaden prey did not change, indicating that the smallest Bluefin Tuna sampled could consume the largest Atlantic Menhaden. We conclude that the relatively small size of forage fishes commonly observed in Bluefin Tuna stomachs was likely due to the high abundance of these fishes in the environment rather than to active selection for small prey. Received August 29, 2013; accepted January 14, 2014